Taxonomy for Trade-off Problem in Distributed Telemedicine Systems - Jánki, Zoltán Richárd; Bilicki, Vilmos (Acta Cybernetica, 2021)
Increasing amount of data and demands for features are challenging for Web systems. By serving these requirements, distributed systems gather ground, however they bring problems along. These issues are already present in telemedicine. Since telemedicine is a wide discipline, various phenomena have different effects on data. Availability and consistency have both important roles in telemedicine, but as CAP and PACELC theorems addressed trade-off problem, no one can guarantee both capabilities simultaneously. Our research aims to get a nearer view of the problem considering real world telemedicine use-cases and offer an easily tunable system with a taxonomy that gives a helping hand at designing telemedicine systems. Model checking verifies and data quality measurement proves the correctness of our model. In the course of measurements, we revealed an interesting occurence and consequence that is called hypothetical-zero-latency.